2010
DOI: 10.1103/physreva.81.043839
|View full text |Cite
|
Sign up to set email alerts
|

Extreme nonlinear electrodynamics in metamaterials with very small linear dielectric permittivity

Abstract: We consider a sub-wavelength periodic layered medium whose slabs are filled by arbitrary linear metamaterials and standard nonlinear Kerr media and we show that the homogenized medium behaves as a Kerr medium whose parameters can assume values not available in standard materials. Exploiting such a parameter availability, we focus on the situation where the linear relative dielectric permittivity is very small thus allowing the observation of the extreme nonlinear regime where the nonlinear polarization is comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 41 publications
0
117
0
Order By: Relevance
“…7,51 Multi-valued solutions of transmittance, reflectance and absorptance at the fundamental frequency are retrieved by using the graphical method outlined in Ref. 52.…”
Section: B Optical Multistability At the Pb Anglementioning
confidence: 99%
See 2 more Smart Citations
“…7,51 Multi-valued solutions of transmittance, reflectance and absorptance at the fundamental frequency are retrieved by using the graphical method outlined in Ref. 52.…”
Section: B Optical Multistability At the Pb Anglementioning
confidence: 99%
“…5,6 This non-resonant enhancement occurs at oblique incidence for transverse magnetic (TM) polarization and is triggered by the continuity of the component of the displacement field normal to the interface. 10 At low irradiance levels, subwavelength ENZ slabs exhibit anomalous multistability and directional hysteresis, 7 so that even a weak nonlinearity can dominate the optical response. Although ENZ conditions occur naturally near the plasma frequency of any material (at visible and UV wavelengths for metals and semiconductors, and in the infrared range for dielectrics), artificial materials are advantageous because ENZ conditions may be engineered at virtually any wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and parameter is obtained by averaging along the y-axis the layer local quantities over the period d) [10]. All effective parameters appearing in the relation (2) can be tailored by choosing the underlying constituents; for example the averaging of the dielectric permittivity can be used to obtain an efficient loss management (using gain and loss media as underlying layers) [12] and/or an epsilon-near-zero metamaterials (exploiting negative and positive dielectric layers) [4].…”
Section: Consider a Monochromatic Transverse Magnetic (Tm) Field (Of mentioning
confidence: 99%
“…On the other hand, a simple strategy for making available the nonlinearity is to reduce the linear polarization. Following this strategy, Ciattoni et al [10] suggested a simple composite structure to achieve very small value of dielectric permittivity where the nonlinear contribution to the dielectric response is not a mere perturbation of the linear one (extreme nonlinear regime). Authors considered a nanoscaled layered structure consisting of alternating metal and dielectric slabs and, in the effective medium scheme, characterized by effective constitutive relations formally coinciding with those of a standard Kerr medium and with response parameters assuming values not available in standard media (nonlinear metamaterials).…”
Section: Introductionmentioning
confidence: 99%